VICTIMOLOGICAL CHARACTERISTICS OF CRIMES WITHIN FAMILY AND DOMESTIC RELATIONS AND MEASURES FOR THEIR PREVENTION - Musurmankulova Iroda Zulpikhorovna (NEW APPROACHES IN EDUCATION: PEDAGOGY, INNOVATION, AND DEVELOPMENT, 2026)
Crimes within family and domestic relations pose a significant threat to social well-being and individual safety, particularly in Uzbekistan where traditional cultural values influence victimization and reporting patterns. This article provides a victimological analysis of family-related crimes, focusing on the vulnerabilities of victims, socio-cultural factors, and institutional challenges. It also examines preventive measures, including legal reforms, public awareness campaigns, and support services designed to protect victims and reduce the incidence of domestic crimes. The findings highlight the need for a multi-faceted approach that combines legal, social, and educational strategies to create safer family environments and uphold victims’ rights.